2020
DOI: 10.3390/jcm9082526
|View full text |Cite
|
Sign up to set email alerts
|

Implications of a Change of Paradigm in Alpha1 Antitrypsin Deficiency Augmentation Therapy: From Biochemical to Clinical Efficacy

Abstract: Ever since the first studies, restoring proteinase imbalance in the lung has traditionally been considered as the main goal of alpha1 antitrypsin (AAT) replacement therapy. This strategy was therefore based on ensuring biochemical efficacy, identifying a protection threshold, and evaluating different dosage regimens. Subsequently, the publication of the results of the main clinical trials showing a decrease in the progression of pulmonary emphysema has led to a debate over a possible change in the main objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…Modes of therapy administration include self-infusion, aerosol, and subcutaneous administration. Gene and recombinant therapies are under development [188,189], and intravenous therapy using α1 antitrypsin derived from human donor plasma has proven to be safe [187].…”
Section: Treatments and New Therapeutic Approachesmentioning
confidence: 99%
“…Modes of therapy administration include self-infusion, aerosol, and subcutaneous administration. Gene and recombinant therapies are under development [188,189], and intravenous therapy using α1 antitrypsin derived from human donor plasma has proven to be safe [187].…”
Section: Treatments and New Therapeutic Approachesmentioning
confidence: 99%
“…Intravenous augmentation therapy with pAAT has, to date, been the only specific treatment for AATD patients with advanced emphysema (3,4). However, studies revealed only modest effects of this therapy; this treatment slowed progression of emphysema as measured by lung density with computed tomography or total lung capacity, but not when measured by functional residual capacity (29).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous repletion of AAT, "augmentation therapy", is recommended for select patients with emphysema, with weekly intravenous infusions of AAT purified from pooled human plasma (pAAT) (3 ,4). However, only modest clinical benefits of augmentation therapy have been reported, and these infusions have been associated with side effects related to infusion of high amounts of protein (3,4). In addition, augmentation therapy is recognized as inconvenient because of the need for frequent infusions and high costs (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the determination of AAT in peripheral blood has some technical conditions that are relevant when interpreting the results well. However, many investigators do not take these differences into account and it is generally assumed that the determination of AAT in blood is equally valid regardless of the laboratory method used [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%